Pola Pendidikan Moral di Panti Asuhan: - Ace Somantri; Ahmad Rifai (LPPM Institut Nasional Laa Roiba Bogor, 2021)
The development of a child cannot be separated from his moral development and morals are formed through early coaching. Therefore, guidance and care for foster children is an obligation that must be carried out. according to experts guidance and parenting is divided into four groups. the first is authoritarian education, both permissive education patterns, the third is democratic education patterns, the fourth is situational education patterns. all four patterns, used to guide children to have good morals. The formulation of the problem in this research is 1) how is the pattern of children's education in the orphanage Aisyiah Rancaekek, 2) how the relationship between educational patterns and morality of foster children in orphanages Aisyah Rancaekek. The research method used in this research is a case study. The results of the study show the pattern of education or guidance used in the orphanage Aisyiah Rancaekek. parenting patterns in orphanages, depending on the caregivers. the first caregiver used an authoritarian pattern and the second caregiver uses a democratic pattern, it can be concluded that the pattern of care used is a situational pattern.